2018
DOI: 10.5812/jjm.62351
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Evaluation of Antifungal Activity of Terbinafine and Terbinafine Nano-Drug Against Clinical Isolates of Dermatophytes

Abstract: Background: Due to long-term treatment of dermatophytic lesions, such as tinea unguium and using antifungal drugs, which cause side effects, it is essential to investigate new antifungal drugs with greater absorption and fewer side effects, such as nanodrugs. Trichophyton rubrum and Microsporum canis are important dermatophyte species. To investigate new strategy treatment, researchers have tried to find a new drug with extensive therapeutic effects and short-duration treatment. In this context, nano-drugs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Similarly, Motedayen et al (2018) evaluated the antifungal activity of terbinafine and terbinafine nano-drug against clinical isolates of dermatophytes and demonstrated that the MIC values of nano-liposomal terbinafine against T. rubrum and M. canis were 0.0156 to 0.25 μ/mL and 0.0078 to 0.125 μ/mL, respectively. In addition, MIC values of terbinafine against T. rubrum and M. canis strains were 0.0625 to 1 μ/mL and 0.0313 to 0.5 μ/mL, respectively (29). That study showed that the nanoparticles of terbinafine had a greater antifungal activity against the T. rubrum and M. canis isolates in comparison with free terbinafine, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Motedayen et al (2018) evaluated the antifungal activity of terbinafine and terbinafine nano-drug against clinical isolates of dermatophytes and demonstrated that the MIC values of nano-liposomal terbinafine against T. rubrum and M. canis were 0.0156 to 0.25 μ/mL and 0.0078 to 0.125 μ/mL, respectively. In addition, MIC values of terbinafine against T. rubrum and M. canis strains were 0.0625 to 1 μ/mL and 0.0313 to 0.5 μ/mL, respectively (29). That study showed that the nanoparticles of terbinafine had a greater antifungal activity against the T. rubrum and M. canis isolates in comparison with free terbinafine, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Multi-drug resistance results primarily from increased expression of genes belonging to the superfamily of ATP-binding cassettes, and primarily ABC transporters, which occur in both prokaryotes and eukaryotes (El-Awady et al 2016; Monod et al 2019). The ABC transporters actively transfer many structurally and chemically diverse compounds across cell membranes through ATP binding and hydrolysis, thereby reducing their accumulation in the cell (Sharma and Prasad 2011;Motedayen et al 2018).…”
Section: Mechanisms Of Resistance To Antifungal Drugsmentioning
confidence: 99%
“…The fungal colonies were covered with 2 mL of Sabouraud’s dextrose broth (SDB) ­followed by a gentle scratching of the agar’s surface with a sterile swab, resulting in a suspension of conidial and hyphal fragments that was transferred to a sterile tube and kept for 5 to 10 minutes at room temperature for sedimentation of heavy particles keeping micro-conidia suspended. Filtration was performed to retain hyphal fragments but permit the passage of dermatophyte micro-conidia to be used later (Motedayen et al., 2018 ). The turbidity of the fungal suspension was measured spectrophotometrically (ultraviolet/visible [UV/VIS] spectrophotometer; JASCO, Tokyo, Japan) at 600 nm and adjusted with SDB to match the 0.5 McFarland standard which is equivalent to 10 5 -10 6 CFU/mL (Marcato et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Plates were incubated at 28 °C for 4 days. Results were evaluated visually (Motedayen et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%